Digitalizing Governance in South Sumatera: An Introduction “E-Sumsel” System Reforming Public Service Management (Jurnal Bina Praja, 2022)
Digitizing government by utilizing the Internet, Communication, and Technology (ICT) is one of the biggest focuses on innovative actions and reforms through various instruments towards improving the quality of public service outcomes. This research discussed the governmental innovation and reform in the South Sumatera Provincial government, which has been trying to increase and improve governmental working transparency and accountability, public management system, and public service improvements known as “E-Sumsel.” By employing qualitative methods, the data collected and extracted from library research such as books, journals as well as the internet. Based on the result, it was found that “E-Sumsel” programs were established to shape digitalizing public management system and for democratic public service transparency and accountability. By focusing on transformations, the South Sumatera provincial government established “E-Sumsel” programs for showing any information about the information such as business opportunities, as well as about the government working. Meanwhile, it has identified several challenges in establishing “E-Sumsel” programs in the South Sumatera government, which remains high-incidence fiefdoms and a strong vertical orientation conspicuous among the governmental agencies. It needs further development to be resolved by creating a new innovative strategy to harmonize the provincial governmental standard operating systems in improving quality public management and public service. For this reason, innovative government action through “E-Sumsel” is very important mode to exist continuously in administrative reform in government institutions with governance innovation that influences each other.